2013
DOI: 10.2741/e682
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis lymphangiogenesis and neurogenesis in endometriosis

Abstract: Endometriosis is a common, benign gynecological disease affecting 10 - 15% of reproductively aged women. It is characterized by the presence of endometrial-like tissue at sites outside the uterus. The most widely accepted theory of endometriosis pathogenesis proposes that shed menstrual endometrium can reach the peritoneum, implant and grow as endometriotic lesions. Angiogenesis, lymphangiogenesis and neurogenesis are implicated in successful ectopic establishment and the generation of endometriosis-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 196 publications
0
38
0
3
Order By: Relevance
“…6,7,28 Recent reports provide evidence that the vascularization of endometriotic lesions is not only driven by angiogenesis but also involves vasculogenesis. 14,15 The latter mechanism of blood vessel development is characterized by homing of circulating EPCs to the lesions, where they are incorporated into the Detailed information about the individual genes is provided in GenBank (http://www.ncbi.nlm.nih.gov/genbank) using the provided accession numbers.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,28 Recent reports provide evidence that the vascularization of endometriotic lesions is not only driven by angiogenesis but also involves vasculogenesis. 14,15 The latter mechanism of blood vessel development is characterized by homing of circulating EPCs to the lesions, where they are incorporated into the Detailed information about the individual genes is provided in GenBank (http://www.ncbi.nlm.nih.gov/genbank) using the provided accession numbers.…”
Section: Discussionmentioning
confidence: 99%
“…74,77,78 Several angiogenic factors in the human endometrium have been identified that play important roles in physiological angiogenesis. [79][80][81][82] The important regulators for endometrial angiogenesis include VEGF, ANGPTs, fibroblast growth factor, thrombospondin, relaxin, adrenomedullin, prostaglandins, prokineticins, angiogenin, and stromal cell-derived factor 1. [83][84][85][86][87][88][89] The VEGF is a key mediator of physiological and pathological vascular remodeling.…”
Section: Angiogenesis (Vascular Maturation)mentioning
confidence: 99%
“…3 Since the survival and proliferation of endometriotic implants require neovascularization, 4 the inhibition of angiogenesis has become an attractive strategy for improved control of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…35 Platelet-derived growth factor B (PDGF-B) is regarded as the main promoter of the pericyte investment in neovessels, being significantly over-expressed by eutopic endometrium of endometriosis patients. 4 Many other ubiquitously expressed molecules have been found to enhance angiogenesis in vitro, in animal models of endometriosis and/ or in human samples. 12,[36][37][38][39][40] Such promoters include cytokines and growth factors secreted by immune and neuroendocrine cells (e.g., interleukins, IL-1β, 6 and 8, tumor necrosis factor-α, TNF-α, and transforming growth factor β, TGF-β).…”
mentioning
confidence: 99%